Health-promoting effects of Lactobacillus-fermented barley in weaned pigs challenged with Escherichia coli K88 +. (20th August 2019) - Koo, B.; Bustamante-García, D.; Kim, J. W.; Nyachoti, C. M.
Abstract : Fermented feeds are being considered as practical alternatives to antimicrobial growth promoters (AGP ) supplemented in nursery pig diets. This study aimed to investigate health-promoting effects of fermented barley in weaned pigs challenged with Escherichia coli K88 + . A total of 37 piglets were weaned at 21 ± 1 day of age (6.41 ± 0.47 kg of BW) and assigned to either of the following five treatment groups: (1) unchallenged control (UCC ; n = 7), (2) challenged control (CC ; n = 7), (3) AGP (CC + 0.1% AGP; n = 7), (4) Ferm1 (challenged and fed homofermentative Lactobacillus plantarum (Homo)-fermented barley; n = 8) and (5) Ferm2 (challenged and fed heterofermentative L . buchneri (Hetero)-fermented barley; n = 8). The control diet included unfermented barley. Barley was fermented with either Homo or Hetero for 90 days under anaerobic conditions. On day 10, all pigs except those in UCC group were orally inoculated with E. coli K88 + (6 × 10 9 colony forming units/ml). The pre-planned orthogonal test was performed to compare (1) UCC and CC, (2) CC and AGP, (3) CC and Ferm1 + Ferm2, as well as (4) Ferm1 and Ferm2. Challenged control pigs showed shorter ( P < 0.05) villus height (VH ) in the duodenum and deeper ( P < 0.05) crypt depth (CD ) in the jejunum than UCC pigs. The AGP group had higher ( P < 0.05) VH and lower ( P < 0.05) IL-6 gene expression in the jejunum compared with CC group. Compared to CC, Ferm1 and Ferm2 had decreased ( P < 0.05) CD in the duodenum, IL-6 gene expression in the jejunum and rectal temperature at 24 h post-challenge. Pigs fed fermented barley diets showed greater ( P < 0.05) faecal abundance of Clostridium Cluster IV and Lactobacilli than those fed UCC diet. Ferm2-fed pigs showed lower ( P < 0.05) concentrations of band cells, eosinophils and lymphocytes at 6, 24 and 48 h after challenge, respectively, and lower ( P < 0.05) faecal abundance of Enterobacteriaceae 24 h after challenge than the Ferm1-fed pigs. In conclusion, the substitution of unfermented barley with fermented barley in a nursery diet showed similar results as those shown by AGP supplementation in terms of enhancing the intestinal morphology and modulating faecal microbiota composition, as well as down-regulating the pro-inflammatory cytokines; therefore, fermented barley can be a possible nutritional strategy for managing nursery pigs fed diets without in-feed AGP.